Non-invasive Cardiac Output Monitoring and Assessment of Fluid Responsiveness in Children With Shock in the Emergency Department - Awadhare, Pranali; Patel, Radha; McCallin, Tracy; Mainali, Kiran; Jackson, Kelly; Starke, Hannah; Bhalala, Utpal (Frontiers in Pediatrics, 2022)
Introduction: Assessment of fluid responsiveness is important in management of shock but conventional methods of assessing fluid responsiveness are often inaccurate. Our study aims to evaluate changes in objective hemodynamic parameters as measured using electrical cardiometry (ICON® monitor) following fluid bolus in children presenting with shock and to evaluate if any specific hemodynamic parameter can best predict fluid responsiveness among children with shock. Materials and methods: We conducted a prospective observational study in children presenting with shock to our emergency department between June 2020 to March 2021. We collected parameters such as heart rate (HR), respiratory rate (RR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and hemodynamic data such as Cardiac Output (CO), Cardiac Index (CI), Index of Contractility (ICON), Stroke Volume (SV), Stroke Index (SI), Corrected Flow Time (FTC), Systolic Time Ratio (STR), Variation of Index of Contractility (VIC), Stroke Volume Variation (SVV), Systemic Vascular Resistance (SVR) and Thoracic Fluid Content (TFC) using the ICON® monitor before and after fluid boluses (FB). We assessed percent change (∆) and used paired-sample student’s t test to compare pre and post hemodynamic data and Mann-Whitney U-test to compare fluid responders and non-responders. p<0.05=significant. Results: We recorded 42 fluid interventions in 40 patients during our study period. The median IQR age was 10.56 (4.8, 14.8) years with male: female ratio 1.2:1. There was significant decrease in ΔRR [-1.61(-14.8, 0); p=0.012], ΔDBP [-5.5 (-14.4, 8); p= 0.027], ΔMAP [-2.2 (-11,2); p=0.018], ΔSVR [-5.8 (-20, 5.2); p=0.025], ΔSTR [-8.39 (-21, 3); p=0.001] and significant increase in ΔTFC [6.2 (3.5, 11.4); p=0.01] following FB. We defined fluid responders by an increase in SV by ≥10% after a single fluid bolus of 20ml/kg crystalloid. Receiver operating curve analysis revealed that among all the parameters, a 15% change in ICON had an excellent AUC (0.85) for the fluid responsiveness. Conclusion: Our study showed significant changes in objective hemodynamic parameters, such as SVR, STR and TFC following fluid bolus in children presenting with shock. A 15% change in ICON had an excellent predictive performance for the fluid responsiveness among our cohort of pediatric shock.